On the Move to Meaningful Internet Systems: OTM 2012 Confederated International Conferences: CoopIS, DOA-SVI, and ODBASE 2012, Rome, Italy, September 10-14, 2012. Proceedings, Part II - Meersman, Robert; Panetto, Herve; Dillon, Tharam; Rinderle-Ma, Stefanie; Dadam, Peter; Zhou, Xiaofang; Pearson, Siani; Ferscha, Alois; Bergamaschi, Sonia; Cruz, Isabel F. (Information Systems and Applications, incl. Internet/Web, and HCI, 2012)
The two-volume set LNCS 7565 and 7566 constitutes the refereed proceedings of three confederated international conferences: Cooperative Information Systems (CoopIS 2012), Distributed Objects and Applications - Secure Virtual Infrastructures (DOA-SVI 2012), and Ontologies, DataBases and Applications of SEmantics (ODBASE 2012) held as part of OTM 2012 in September 2012 in Rome, Italy. The 53 revised full papers presented were carefully reviewed and selected from a total of 169 submissions. The 31 full papers included in the second volume constitute the proceedings of DOA-SVI 2012 with 10 full papers organized in topical sections on privacy in the cloud; resource management and assurance; context, compliance and attack; and ODBASE 2012 with 21 full papers organized in topical sections on using ontologies and semantics; applying probalistic techniques to semantic information; exploiting and querying semantic information; and managing and storing semantic information.